SOSIALISASI SANITASI LINGKUNGAN HIDUP SEHAT BAGI MASYARAKAT DESA BAOBOLAK KABUPATEN LEMBATA - Meze Ule, Dionisius; Nahak, Amelia; Simon H. Molan, Kristianus; PerdanaAyu Lawalu , Stephanie; Likusina Kaha, Hedrikus; Idriyati, Idriyati (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service activity was carried out in Baobolak Village, Nagawutung District, Lembata Regency, East Nusa Tenggara, with the main objective of increasing public awareness of the importance of healthy and sustainable environmental sanitation. This village faces various serious obstacles related to access to clean water and adequate sanitation facilities, as well as low awareness of clean and healthy living behavior among residents. Through a participatory and educational approach, the community is actively involved from the planning stage to the evaluation of activities. Socialization is carried out through direct counseling, group discussions, and demonstrations of sanitation practices such as proper hand washing, effective waste management, and the use of healthy toilets that meet standards. In addition, field observations were carried out to assess sanitation conditions and identify the main problems faced. The results of the activity showed an increase in public understanding of the importance of sanitation and environmental cleanliness, as well as the growth of collective awareness to maintain environmental cleanliness in a sustainable manner. This intervention is expected to encourage positive, sustainable behavioral changes, reduce the risk of disease, and create a healthy environment as an important foundation for economic and social development in Baobolak Village.